Effect of Irrigation Time of Antiseptic Solutions on Bone Cell Viability and Growth Factor Release. Issue 2 (March 2018) - Sawada, Kosaku; Nakahara, Ken; Haga-Tsujimura, Maiko; Fujioka-Kobayashi, Masako; Iizuka, Tateyuki; Miron, Richard J.
Abstract : Abstract: Antiseptic solutions are commonly utilized to treat local infection in the oral and maxillofacial region. However, surrounding vital bone is also exposed to antiseptic agents during irrigation and may have a potential negative impact on bone survival. The aim of the present study was therefore to investigate the effect of rinsing time with various antiseptic solutions on bone cell viability, as well as their subsequent release of growth factors important for bone regeneration. The bone samples collected from porcine mandible were rinsed in the following commonly utilized antiseptic solutions; povidone-iodine (0.5%), chlorhexidine digluconate (CHX, 0.2%), hydrogen peroxide (1%), and sodium hypochlorite (0.25%) for 1, 5, 10, 20, 30, or 60 minutes and assessed for cell viability and release of growth factors including vascular endothelial growth factor, transforming growth factor beta 1, bone morphogenetic protein 2, receptor activator of nuclear factor kappa-B ligand, and interleukin-1 beta by enzyme-linked immunosorbent assay. It was found in all the tested groups that the long exposure of any of the tested antiseptic solutions drastically promoted higher cell death. Sodium hypochlorite demonstrated the significantly highest cell death and at all time points. Interestingly, bone cell viability was highest in the CHX group post short-term rinsing of 1, 5, or 10 minutes when compared with the other 4 tested groups. A similar trend was also observed in subsequent growth factor release. The present study demonstrated that of the 4 tested antiseptic solutions, short-term CHX rinsing (ideally within 1 minute) favored bone cell viability and growth factor release. Clinical protocols should be adapted accordingly.